2013
DOI: 10.1038/emboj.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

The chromodomain helicase Chd4 is required for Polycomb-mediated inhibition of astroglial differentiation

Abstract: Polycomb group (PcG) proteins form transcriptional repressor complexes with well-established functions during cell-fate determination. Yet, the mechanisms underlying their regulation remain poorly understood. Here, we extend the role of Polycomb complexes in the temporal control of neural progenitor cell (NPC) commitment by demonstrating that the PcG protein Ezh2 is necessary to prevent the premature onset of gliogenesis. In addition, we identify the chromodomain helicase DNA-binding protein 4 (Chd4) as a crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 65 publications
1
88
0
Order By: Relevance
“…However, examination of published data does not reveal any examples in which NuRD-independent activity has clearly been demonstrated. Nevertheless, one recent study does demonstrate that an interaction between CHD4 and the histone methyltransferase Ezh2, a core component of the Polycomb repression complex, is essential for the ability of Polycomb to repress the gene GFAP during astroglial differentiation (52). In an Ezh2-directed affinity purification experiment, CHD4 was detected by Western blot, but neither MTA2 nor MBD3 were observed, suggesting that this interaction does not involve the full NuRD complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, examination of published data does not reveal any examples in which NuRD-independent activity has clearly been demonstrated. Nevertheless, one recent study does demonstrate that an interaction between CHD4 and the histone methyltransferase Ezh2, a core component of the Polycomb repression complex, is essential for the ability of Polycomb to repress the gene GFAP during astroglial differentiation (52). In an Ezh2-directed affinity purification experiment, CHD4 was detected by Western blot, but neither MTA2 nor MBD3 were observed, suggesting that this interaction does not involve the full NuRD complex.…”
Section: Discussionmentioning
confidence: 99%
“…While the minimal deleted region contains CHD8 and the adjacent SUPT16H locus, the importance of abrogated CHD8 function in the phenotype of these patients is underscored by the identification of disruptive CHD8 mutations in individuals with DD or ASD [31] and recapitulation of a subset of features of the human phenotype in the zebrafish model [32]. Although other CHD proteins have yet to be linked to human genetic disease, it has been demonstrated that CHD4 and CHD5 carry out important functions in neurogenesis [33,34]. Although beyond the scope of this communication, the contribution of CHD dysfunction in the etiology of cancer has been long recognized [35].…”
Section: Chd Family and Genetic Diseasementioning
confidence: 99%
“…CHD4, CHD5, and CHD7 play pivotal roles in the function and differentiation of neural stem cell niches in the subventricular zone (SVZ) of the forebrain and dentate gyrus of the hippocampus through cooperation with major epigenetic modifiers, transcription factors, and signaling pathways. During cortical neurogenesis, CHD4 is expressed in murine SVZ neural progenitor cells and interacts with the Polycomb Repressive Complex 2 (PRC2), specifically with the H3K27 methyltransferase enzyme, Enhancer of Zeste 2 [45,46]. The CHD4/ PRC2 complex directly binds to the promoter of the glial fibrillary acidic protein (GFAP) gene (Gfap), represses its expression, and prevents glial differentiation [46].…”
Section: Chd Proteins and Neural Stem Cellsmentioning
confidence: 99%
“…During cortical neurogenesis, CHD4 is expressed in murine SVZ neural progenitor cells and interacts with the Polycomb Repressive Complex 2 (PRC2), specifically with the H3K27 methyltransferase enzyme, Enhancer of Zeste 2 [45,46]. The CHD4/ PRC2 complex directly binds to the promoter of the glial fibrillary acidic protein (GFAP) gene (Gfap), represses its expression, and prevents glial differentiation [46]. Through inhibition of the Gfap locus, CHD4 and PRC2 promote neuronal differentiation during the neurogenic period (between embryonic days 11 and 18 in mice) [46].…”
Section: Chd Proteins and Neural Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation